1997
DOI: 10.1111/j.1745-4557.1997.tb00463.x
|View full text |Cite
|
Sign up to set email alerts
|

STORAGE OF ‘SWEETHEART’ CHERRIES IN SEALED PLASTIC FILM1

Abstract: Sweetheart ' cherries were sealed in peiforated or nonperforatedpolyethylene bags and stored for 6 weeks in air at OC. Samples were removed after 1, 2, 4 and 6 weeks of storage and evaluated for fruit and sensory quality. Volatile analyses were done on samples kept in storage for 2, 4, 6, 8 and 9 weeks. Atmospheres afrer 6 weeks of storage were approximately 4.6% 0, and 10% CO, for the peiforated bags (1993) and 6.6% 0, and 3.5% CO, for the non-peiforated bags (1994). Fruit brightness (L* value), firmness and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
37
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 3 publications
6
37
1
Order By: Relevance
“…By comparison, Wang and Verstheim (2002) found that the TA of the fruit of six sweet cherry cultivars stored either in 10% CO 2 or in 5% CO 2 did neither differ significantly from each other nor from the TA of the fruit stored in normal atmosphere. Meheriuk et al (1995Meheriuk et al ( , 1997 did not find any effect of atmospheric composition on acidity changes in cherries, while other studies pointed out that low oxygen levels reduced the acid content (Jiang et al 2002).…”
Section: Resultsmentioning
confidence: 63%
See 1 more Smart Citation
“…By comparison, Wang and Verstheim (2002) found that the TA of the fruit of six sweet cherry cultivars stored either in 10% CO 2 or in 5% CO 2 did neither differ significantly from each other nor from the TA of the fruit stored in normal atmosphere. Meheriuk et al (1995Meheriuk et al ( , 1997 did not find any effect of atmospheric composition on acidity changes in cherries, while other studies pointed out that low oxygen levels reduced the acid content (Jiang et al 2002).…”
Section: Resultsmentioning
confidence: 63%
“…Comparing fruit firmness after the storage period with that at harvest time, we found that, generally, sweet cherries became softer after storage. Some other authors had demonstrated the ability of sweet cherries to maintain firmness for up to 8 weeks of storage (Meheriuk et al 1995) or even increase their firmness after MA storage (Meheriuk et al 1997, Kappel et al 2002. The finding that high CO 2 concentration and low temperature promote higher fruit firmness is also confirmed by other researchers (Jiang et al 2002, Goliáš et al 2006.…”
Section: Resultsmentioning
confidence: 99%
“…Some researchers point out that both in controlled atmosphere chambers and in modified atmosphere packaging there is a sharp decrease in acidity throughout the storage life of cherries. 1,2,28 In some cases, however, this reduction occurs only at the end of the storage period. 5 The effect of low O 2 concentration on these results is not conclusive.…”
Section: Results and Discussion Soluble Solids And Aciditymentioning
confidence: 99%
“…8 The preservation of cherries in low-O 2 atmospheres maintains the fresh external appearance, the acidity level and the green colour of the stem. 3,4 Although some previous studies have been conducted on MAP and CA storage of cherries, 1,4 recommendations about CO 2 and O 2 levels are inconsistent. Several authors report that CO 2 concentrations between 10 and 15% and O 2 concentrations between 3 and 10% are adequate for cherry preservation.…”
Section: Introductionmentioning
confidence: 99%
“…MAP induces a delay in the physicochemical changes related to fruit quality loss by increasing the level of CO 2 and decreasing the O 2 content. However, different O 2 (2-10%) and CO 2 (5-20%) concentrations have been reported to be optimal for different cherry cultivars (Kupferman & Sanderson, 2001;Meheriuk et al, 1997;Remó n, Ferrer, Maquina, Burgos, & Oria, 2000;Remó n, Venturini, Ló pez-Buesa, & Oria, 2003;Spotts, Cervantes, & Facteau, 2002;Tian, Fan, Xu, Wang, & Jiang, 2001). These discrepancies could be related to cultivar itself or ripening stage at harvest.…”
Section: Introductionmentioning
confidence: 87%